2011
DOI: 10.5586/asbp.2011.018
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptile length and plant height of modern tall and semi-dwarf European winter wheat varieties

Abstract: A total of 124 recent winter wheat accessions of European origin were screened for coleoptile length and plant height. Most of the accessions (74.2%) possessed a coleoptile length ranging between 5.00 and 7.00 cm. The German varieties Ebi, Pegassos, Flair without Rht genes had a coleoptile length of 9.08, 9.43, 9.56 cm and a plant height of 97, 95 and 98 cm, respectively. The Serbian variety Pobeda possessing Rht8 had a coleoptile length of 9.14 cm and a plant height of 71 cm. The varieties possessing Rht-B1b,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(63 reference statements)
7
6
0
Order By: Relevance
“…These results are in accordance with the earlier reports [38]. Coleoptile length and plant height are polygenic traits and many QTLs have been reported that influence traits [26], [28], [39][41]. We also observed a full range of plant heights in particular coleoptile class e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with the earlier reports [38]. Coleoptile length and plant height are polygenic traits and many QTLs have been reported that influence traits [26], [28], [39][41]. We also observed a full range of plant heights in particular coleoptile class e.g.…”
Section: Discussionsupporting
confidence: 93%
“…The pleiotropic effects associated with GA insensitive mutants on early growth have been reported and coleoptile length was positively correlated with plant height at maturity [6], [8], [26]. The major phenotypic effect quantitative trait loci (QTL) for coleoptile length were mapped on the short arm of 4B and 4D chromosomes in the close proximity of dwarfing genes, thus accounting for the pleotropic effect of dwarfing genes on coleoptile length [27].…”
Section: Introductionmentioning
confidence: 99%
“…We also screened F 2:3 mutant seeds to investigate the impact of the nonsense mutations on coleoptile length and GA responsiveness (Table 2). We observed the previously reported impact of Rht-B1b and Rht-D1b, which reduced coleoptile length 43% compared with Rht-1a (Amram et al, 2015;Liatukas & Ruzgas, 2011). Furthermore, coleoptile length of Rht-B1b and Rht-D1b was not affected by the presence of GA, as previously reported (Amram et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…For example, in a comparison of nine semidwarf and seven tall wheat genotypes sown at depths, Rebetzke et al (2007b) detected no significant correlation between CL and PH among the tall wheat varieties (Rebetzke et al, 2007b). In contrast, a positive correlation has been observed between PH and CL in wheat bearing the GA-insensitive dwarfing genes Rht1 and Rht2 (Rebetzke et al, 2007b;Liatukas and Ruzgas, 2011), which have the effect of suppressing CL and PH (Ellis et al, 2004). In the present study, we identified a total of 229 significant markers for the eight assessed agronomic traits based on GWAS (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 98%